Integrated project delivery with blockchain: An automated financial system - Elghaish, Faris; Abrishami, Sepehr; Hosseini, M. Reza (Automation in construction, 2020)
Integrated project delivery (IPD) in the architecture, engineering and construction (AEC) industry relies on risk/reward sharing and deferral of parties' profit payments until all project activities are completed. A decentralised, automated and secured financial platform is needed to enable all parties to control and track financial transactions, with no unauthorised changes allowed. The new technology, blockchain, enables data to be recorded, has no network participant with dominant power and manages data using specific functions, in line with smart contracts. The present study is the first to develop a framework proposing blockchain technology utilisation in IPD projects. The framework would enable core project team members to automatically execute all financial transactions, through coding the three main transactions of IPD projects: reimbursed costs, profit and cost saving, as functions of the IPD smart contract. To demonstrate the proposed framework's applicability, a “proof of concept” is developed and validated through an IPD case project. The practicality of the built-up hyperledger network (IBM® Blockchain Cloud Beta 2) and the advantages of the proposed smart contract functions are examined. The user-friendliness of the proposed financial system and its efficiency in automating all transactions are demonstrated. No deficiency is found in the blockchain network components. The study's findings, applied in a favourable external context, would facilitate IPD adoption and use across the AEC industry by providing a workable solution to existing financial barriers. The findings extend the horizon for further research on exploring blockchain's capabilities to solve comparable deficiencies to those affecting the AEC industry. •Developing logical operators to estimate key IPD financial transactions (reimbursed cost, profit and cost saving), applicable to typical scenarios.•Proposing a methodology to enhance financial transaction management and risk/reward sharing practices in IPD.•Creating a toolset through BIM/blockchain integration, to provide an automated financial platform for IPD.•Creating blueprints for blockchain-enabled smart contracts for construction projects•Introducing a use case for hyperledger fabric application in IPD financial management.